2019
DOI: 10.1016/j.cell.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification and Comparative Taxonomics of Foveal and Peripheral Cells in Primate Retina

Abstract: High-acuity vision in primates, including humans, is mediated by a small central retinal region called the fovea. As more accessible organisms lack a fovea, its specialized function and its dysfunction in ocular diseases remain poorly understood. We used 165,000 single-cell RNA-seq profiles to generate comprehensive cellular taxonomies of macaque fovea and peripheral retina. More than 80% of >60 cell types match between the two regions but exhibit substantial differences in proportions and gene expression, som… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
447
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(505 citation statements)
references
References 85 publications
52
447
4
2
Order By: Relevance
“…Moreover, the transcription factor TBX2 has been implicated in subtype specification of Sws1 ‐cones in zebrafish and chicken (Alvarez‐Delfin et al , ; Enright et al , ). In support of these studies, our data showed that TBX2 marks the S‐cones in humans, which is also conserved in macaque (Peng et al , ). Together, these results detailed the molecular profiles and identified marker genes that can distinguish the cone subtypes in humans.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the transcription factor TBX2 has been implicated in subtype specification of Sws1 ‐cones in zebrafish and chicken (Alvarez‐Delfin et al , ; Enright et al , ). In support of these studies, our data showed that TBX2 marks the S‐cones in humans, which is also conserved in macaque (Peng et al , ). Together, these results detailed the molecular profiles and identified marker genes that can distinguish the cone subtypes in humans.…”
Section: Resultssupporting
confidence: 85%
“…We analyzed scRNA-seq data following the pipeline detailed in Peng et al (2019). Briefly, sample demultiplexing was performed with cellranger mkfastq function (version 2.1.0; 10X Chromium), and reads were aligned to the reference genome mm10 v1.2.0 from cellranger refdata using the cellranger count function with the option --force-cells=6000.…”
Section: Methodsmentioning
confidence: 99%
“…A shallow sequencing of large cell numbers facilitates comprehensive classification more than a deep sequencing of a small number of cells. Recent scRNA‐seq studies in human and primate adult retina provided a reference transcriptome specific for retinal cell type and offered an advanced discrimination of the mechanisms defining the retinal identity . In primate retina, Peng and colleagues distinguished more than 70 cell types, included extremely rare cell types such as intrinsically photosensitive RGCs, which constitute less than the 0.002% of all the retinal cells .…”
Section: Rare Cell Types and Neuron‐specific Enhancers Can Be Identifmentioning
confidence: 99%
“…Recent scRNA‐seq studies in human and primate adult retina provided a reference transcriptome specific for retinal cell type and offered an advanced discrimination of the mechanisms defining the retinal identity . In primate retina, Peng and colleagues distinguished more than 70 cell types, included extremely rare cell types such as intrinsically photosensitive RGCs, which constitute less than the 0.002% of all the retinal cells . Description of rare cell‐types is particularly thorough when purified cell populations are used as starting material for single‐cell sequencing.…”
Section: Rare Cell Types and Neuron‐specific Enhancers Can Be Identifmentioning
confidence: 99%